SCIENTIFIC SUBSTANTIATION OF THE OSTEOSYNTHESIS METHOD CONVERSION IN LONG BONES GUNSHOT FRACTURES IN THE ARMED FORCES MEDICAL SYSTEM OF UKRAINE - Khomenko, I.P.; Korol, S.O.; Lurin, I.A.; Chelishvili, A.L.; Sichinava, R.M. (World of Medicine and Biology, 2019)
The purpose of the work was to improve the results of treatment of inflammatory fractures of the long bones by introducing external osteosynthesis conversion to internal. An array of studies consisted of 290 wounded with gunshot fractures of the long bones of the extremities, which were damaged in 2014-2018 when conducting an anti-terrorist operation. Upon admission to the second level, 118 (40.7%) of the wounded patients underwent conversion of an external fixation rod apparatus to internal osteosynthesis, and 172 (59.3%) were the final treatment method. Osteosynthesis conversion resulted in an increase in good functional results by 20.8% and a decrease in the relative number of unsatisfactory ones by 11.9% (pα
Keywords: function restoration; inflammatory fractures; method conversion; bone osteosynthesis; health care system